Resistance Patterns Associated with HCV NS5A Inhibitors Provide Limited Insight into Drug Binding - Moheshwarnath Issur; Matthias Götte (Viruses, 2014)
Direct-acting antivirals (DAAs) have significantly improved the treatment of infection with the hepatitis C virus. A promising class of novel antiviral agents targets the HCV NS5A protein. The high potency and broad genotypic coverage are favorable properties. NS5A inhibitors are currently assessed in advanced clinical trials in combination with viral polymerase inhibitors and/or viral protease inhibitors. However, the clinical use of NS5A inhibitors is also associated with new challenges. HCV variants with decreased susceptibility to these drugs can emerge and compromise therapy. In this review, we discuss resistance patterns in NS5A with focus prevalence and implications for inhibitor binding.